Interferon-γ and Tumor Necrosis Factor-α Mediate the Upregulation of Indoleamine 2,3-Dioxygenase and the Induction of Depressive-Like Behavior in Mice in Response to Bacillus Calmette-Guérin - O'Connor, Jason C. (Society for Neuroscience, 2009)
Although the tryptophan-degrading enzyme, indoleamine 2,3-dioxygenase (IDO), is a pivotal mediator of inflammation-induced depression, its mechanism of regulation has not yet been investigated in this context. Here, we demonstrate an essential role for interferon (IFN)γ and tumor necrosis factor (TNF)α in the induction of IDO and depressive-like behaviors in response to chronic immune activation. Wild-type (WT) control mice and IFNγR(−−) mice were inoculated with an attenuated form of Mycobacterium bovis, bacille Calmette-Guérin (BCG). Infection with BCG induced an acute episode of sickness that was similar in WT and IFNγR(−−) mice. Increased immobility during the forced swim and tail suspension tests occurred in WT mice 7 d after BCG inoculation but was entirely absent in IFNγR(−−) mice. In WT mice, these indices of depressive-like behavior were associated with chronic upregulation of IFNγ, interleukin(IL)-1β, TNFα, and IDO. Proinflammatory cytokine expression was elevated in BCG-infected IFNγR(−−) mice as well, but upregulation of lung and brain IDO mRNA was completely abolished. This was accompanied by an attenuation of BCG-induced TNFα mRNA and the lack of an increase in plasma kynurenine/tryptophan ratio in the BCG-inoculated IFNγR(−−) mice compared with WT controls. Pretreatment of mice with the TNFα antagonist, etanercept, partially blunted BCG-induced IDO activation and depressive-like behavior. In accordance with these in vivo data, IFNγ and TNFα synergized to induce IDO in primary microglia. Together, these data demonstrate that IFNγ, with TNFα, is necessary for induction of IDO and depressive-like behavior in mice after BCG infection.